DESIGN OF DEVELOPMENT OF SEMIELLIPTIC CRACK IN BODY OF BORING PIPE AT THE USE IN ARRANGEMENT VIBROPROTECTIVE DEVICES - Тирлич, Володимир Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The task of calculation of remaining longevity of boring pipe is examined, that contains the initial defect of type of half elliptic crack. A task got untied step by step: on the first stage, by the method of eventual elements the tense deformed consisting of cut of boring column was determined, where a crack is, and basic data for a next stage turn out. On the second stage, as a result of numeral design, got sizes of coefficients of intensity of tensions for the cracks of different sizes. On a finishing stage, taking into account results got on previous stages, kinetics of fatigue half elliptic crack, which remaining longevity of the damaged pipe is determined on the basis of, is explored. Calculations were conducted in two variants: with the use of vibroprotective built on and without them.